Influence of Organic Matter on Gas-Bearing Properties and Analysis of Sedimentary Mechanism of Organic Matter Enrichment: A Case Study on the Yangtze Region of Southern China during the Early Cambrian - Qinyu Li; Kun Zhang; Lin Wei; Dahai Wang; Zhiyuan Chen; Xiangdong Yin; Fengli Han; Pei Liu; Liangyi Tang; Xuejiao Yuan (Geofluids)
Shale gas exploration requires studies on the enrichment mechanism of sedimentary organic matter. The Lower Cambrian shale is taken as a study object to analyze the effect of organic matter on gas content using TOC content and porosity analyses, isothermal adsorption experiments, and FIB-HIM scanning electron microscopy observations. Then, we selected typical wells to determine the presence of excessive silica in the siliceous minerals by quantitative calculations. Besides, we analyzed the genesis of excessive siliceous minerals using elements including Al, Fe, and Mn, thus speculating the controlling factors of the redox environment and biological productivity. Results show that total organic carbon content controls the content of free and adsorbed gas, while shale gas mainly exists in organic pores and is developed in large numbers and with high roundness, showing the characteristics of “small pores inside big pores.” In the Lower Yangtze region during the Early Cambrian, the excessive siliceous minerals were of hydrothermal origin, and there were frequent hydrothermal activities due to its closeness to plate boundaries. These activities can intensify the reducibility of the waterbody’s bottom and improve the biological productivity on its surface, resulting in the enrichment of this matter. Most excessive silicon in this region is biogenic, while only a small part is of hydrothermal and biogenic mixed origin. The enclosed waterbody of the Upper Yangtze region was far from plate boundaries and close to the semiclosed “gulf,” resulting in its delamination. The waterbody’s surface was abundant with oxygen, thus increasing the biological productivity, while the high reducibility at the waterbody’s bottom was conducive to preserving sedimentary organic matter.